Principal’s Academic Supervision Management of Teachers’ Performance - Putri, Yuli Husnita (PPSDP International Journal of Education, 2025)
Talking about education cannot be separated from the term quality. The quality indicator itself can be measured by supervision activities that can be carried out by the principal as the leader of the institution as a body that accommodates community aspirations regarding improving the quality of education. The role of the principal should be able to make breakthroughs in terms of managing teachers’ performance. This is a library research, that utilizes library sources that are carried out by tracing and reviewing primary and secondary literature, books on academic supervision, the role of the principal and school committee, building a climate of cooperation and other scientific papers. The results state that the success of the principal in improving teachers’ performance is highly dependent on the supervision management carried out including the stages of preparation, implementation, evaluation and follow-up. The ability of the principal to build a good climate of cooperation with the school community will make it easier for his institution to achieve common policies and goals in terms of controlling the quality of education in his institution on an ongoing basis. This article concludes the management of academic supervision of the principal could improve teachers’ performance.